Study the Vital Activity of Some the Prepared Cinnamaldehyde Derivatives - M. Aburzeza , Moktar; R. Albakoush, Atiga (Journal of Neonatal Surgery, 2025)
Five compounds were synthesized, which are derivatives of cinnamaldehyde, including P-ethoxy cinnamaldehyde, referred to as compound (a) From it, compounds (b, c, d, and e) were obtained by combining it with a group of compounds and using specific solvents suitable for each preparation. They were also characterized using IR, H1NMR and C13NMR with CDCl3. To demonstrate their biological efficacy, we will study their effects on various types of bacteria as well as cancer cell lines and fungal of type Penicillium